2004
DOI: 10.1128/aac.48.1.151-160.2004
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation by Stenotrophomonas maltophilia : Modulation by Quinolones, Trimethoprim-Sulfamethoxazole, and Ceftazidime

Abstract: We investigated the in vitro effects of seven fluoroquinolones (ciprofloxacin, grepafloxacin, levofloxacin, moxifloxacin, norfloxacin, ofloxacin, and rufloxacin), compared to those of trimethoprim-sulfamethoxazole (SXT) and ceftazidime on total biomass and cell viability of Stenotrophomonas maltophilia biofilm. S. maltophilia attached rapidly to polystyrene, within 2 h of incubation, and then biofilm formation increased over time, reaching maximum growth at 24 h. In the presence of fluoroquinolones at one-half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
137
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(147 citation statements)
references
References 35 publications
8
137
0
2
Order By: Relevance
“…Moreover, the isolates related to B. toyonensis could exhibit flocculating activity (Okaiyeto et al, 2015). All strains isolated from aerobic tank are wastewater bacteria known for exhibiting efficient heterotrophic nitrificationeaerobic denitrification ability at a wide range of ammonium loads and producing biofilm (Di Bonaventura et al, 2004;Wang et al, 2010;Chen et al, 2012;Ren et al, 2014).…”
Section: Membrane Filtration Propertiesmentioning
confidence: 99%
“…Moreover, the isolates related to B. toyonensis could exhibit flocculating activity (Okaiyeto et al, 2015). All strains isolated from aerobic tank are wastewater bacteria known for exhibiting efficient heterotrophic nitrificationeaerobic denitrification ability at a wide range of ammonium loads and producing biofilm (Di Bonaventura et al, 2004;Wang et al, 2010;Chen et al, 2012;Ren et al, 2014).…”
Section: Membrane Filtration Propertiesmentioning
confidence: 99%
“…This lends credence to the use of selenium or heavy metal-containing medications in TV for their ability to disperse biofilms [19,20,21]. Fluoroquinolones are known to be effective against P. aeruginosa biofilm formation through their ability to induce apoptosis in normally apoptotic-resistant persister cells [9,22]. Newer molecules such as dispersin B, alginate lysate, sodium nitroprusside, and diguanylate cyclase enzymes have been found to be effective bacterial biofilm dispersal agents in vitro.…”
Section: Sample Collection and Processingmentioning
confidence: 99%
“…It has been suggested that biofilms may be the source of relapse of so-called "noninfectious" diseases such as acne vulgaris, atopic dermatitis, miliaria, and onychomycosis after the termination of antimicrobial treatment [8]. Nondividing persister cells residing within the biofilms may be responsible for reseeding biofilms post-treatment as they are immune to most antimicrobial agents and can deactivate their apoptosis pathway [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…Serratia and Stenotrophomonas spp. are often reported as being members of biofilm-forming bacteria (Bonaventura et al 2004, Labbate et al 2004) and of activated sludge-derived microbial communities (Assih et al 2002, Du et al 2008). …”
Section: Establishment Of An Isolates Mixture That Consistently Degramentioning
confidence: 99%